Modificação da lignina acetossolve para aplicação como agente antioxidante - Araújo Junior, Celso Pires de (2020)
Several oil palm trees thrive in the hot and humid climate of the climatic regions. Among them are the oil palm (Elaeis guineensis), which is the main source of palm and palm kernel oil. The oil palm pie (mesocarp), rich in line, is a co-product of oil extraction. Lignin has antioxidant and anti-UV properties; therefore, it has great potential to be used as an antioxidant. The objective of this work was to characterize and evaluate the application of alkylated acetosolve lignin obtained from palm oil as an antioxidant in Pickering emulsions. Auto-hydrolysed acetosolve lignin (LA) an additional step of auto-hydrolysis in a high pressure reactor was performed before the conventional acetosolve process. The products were obtained by Friedel-Crafts alkylation of the lignins. Analyzes of GPC, FTIR, NMR, TGA, DSC, and antioxidant activity were performed. The products obtained had greater antioxidant activity than the raw material, which were confirmed by the DPPH, ABTS and FRAP methods. Pickering emulsions with nanofibrillated bacterial cellulose showed high stability, with no phase separation, even over 60 days of storage. The cytotoxicity tests showed a high percentage of viable cells for the alkylated products up to a concentration of 60 µg/mL, which represents more than three times the concentration of the products needed to act as antioxidants in cosmetics. BHT for concentrations at which it is used as an antioxidant showed cytotoxicity. Thus, the application of alkylated lignin in Pickering emulsions is very promising.